Glycosylation in cardenolide biosynthesis. - Theurer, Christoph; Treumann, Hans-Joachim; Faust, Thomas; May, Ursula; Kreis, Wolfgang (Plant Cell Tissue and Organ Culture, 1994)
The glycosylation and deglycosylation of cardiac glycosides was investigated using cell suspension cultures and shoot cultures, both established from Digitalis lanata EHRH. plants, as well as isolated enzymes. Shoots were capable of glucosylating digitoxigenin, evatromonoside, digiproside, glucodigitoxigenin and digitoxin. Suspension cultured Digitalis cells glucosylated all the substrates mentioned but digiproside, whereas the UDP-glucosedependent cardinolide glucosyltransferase isolated from that source did not accept digitoxigenin and digiproside as substrates. It is concluded that at least three different glucosyltransferases are involved in cardiac glycoside formation in Digitalis. Similar experiments carried out with glucosylated cardenolides which were administered to cultured cells, shoots and a cardenolide β-glucosidase isolated from young leaves revealed that at least two different glucosidases occur in Digitalis lanata, albeit in different tissues or during different phases of development. The biotransformation of glucoevatromonoside was investigated using unlabelled compound and [14C-glucose]-glucoevatromonoside synthesized enzymatically. After 7 d of incubation almost no radioactivity could be recovered from the cardenolide fraction, indicating that the terminal glucose of glucoevatromonoside was now incorporated into volatile, hydrophilic and insoluble compounds. Since, on the other hand, large amounts of cardenolides were found in the experiments with unlabelled glucoevatromonoside it is assumed that steady state or pool size regulation is achieved by the coordinated action of a cardenolide glucosidase and a glucosyltransferase. © 1994 Kluwer Academic Publishers.
UnivIS-Import:2015-03-05:Pub.1994.nat.dbio.LPB.glycos
Keywords: β-glucosidase; biotransformation; cardiac glycosides; Digitalis lanata; glucosyltransferase; radiolabelled cardiac glycosides